2022
DOI: 10.1371/journal.pone.0267181
|View full text |Cite
|
Sign up to set email alerts
|

Convergent validity of the Autism Spectrum Disorder Mealtime Behavior Questionnaire (ASD-MBQ) for children with autism spectrum disorder

Abstract: There was a growing interest in difficulties with eating as one of the most problematic symptoms in children with autism spectrum disorder (ASD). The purpose of this study is to examine the convergent validity of the Autism Spectrum Disorder Mealtime Behavior Questionnaire (ASD-MBQ) with the Asahide’s test for social adjustment skills, the Japanese version of the short version of the sensory profile questionnaire, the Japanese version of the Social Communication Questionnaire, and the Parenting Strain Index in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The number of autistic subjects included in each study ranged from one ( Biller et al, 2022 ; Biller & Johnson, 2020 ; Kim & Seung, 2015 ; Petinou, 2021 ) to 294 ( Nakaoka et al, 2022 ), with nine additional papers including over one hundred autistic subjects ( Demartini et al, 2021 ; Gal et al, 2022 ; Gernsbacher et al, 2008 ; Leader et al, 2020 ; Mandelbaum et al, 2006 ; Manfredonia et al, 2019 ; Parmeggiani et al, 2019 ; Vashdi, 2014 ; Vissoker et al, 2019 ). Eighteen studies (17%) included a sample of fewer than 10 autistic subjects, 27 studies (25%) had a sample size of 10–20 autistic subjects, 24 studies (22%) had a sample size of 21–30 autistic subjects, 13 studies (12%) had a sample size of 31–50, and 25 studies (23%) had a sample size of over 50 autistic subjects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of autistic subjects included in each study ranged from one ( Biller et al, 2022 ; Biller & Johnson, 2020 ; Kim & Seung, 2015 ; Petinou, 2021 ) to 294 ( Nakaoka et al, 2022 ), with nine additional papers including over one hundred autistic subjects ( Demartini et al, 2021 ; Gal et al, 2022 ; Gernsbacher et al, 2008 ; Leader et al, 2020 ; Mandelbaum et al, 2006 ; Manfredonia et al, 2019 ; Parmeggiani et al, 2019 ; Vashdi, 2014 ; Vissoker et al, 2019 ). Eighteen studies (17%) included a sample of fewer than 10 autistic subjects, 27 studies (25%) had a sample size of 10–20 autistic subjects, 24 studies (22%) had a sample size of 21–30 autistic subjects, 13 studies (12%) had a sample size of 31–50, and 25 studies (23%) had a sample size of over 50 autistic subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Interviews or questionnaires of autistic individuals or their caregivers were used in 14 studies (13%; Ashley et al, 2020 ; Demartini et al, 2021 ; Gal et al, 2022 ; Gernsbacher et al, 2008 ; Leader et al, 2020 ; Lundin Remnélius et al, 2022 ; Nakaoka et al, 2022 ; Shriberg et al, 2010 ; Spek et al, 2020 ; Stevenson et al, 2017 ; Thurm et al, 2007 ; van Dijk et al, 2021 ; Velleman et al, 2010 ; Vissoker et al, 2019 ). Nine of these studies (64%) reported a deficit in some measure of oromotor functioning among their autistic sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The utilization of the Brief Autism Mealtime Behavior Inventory (BAMBI) questionnaire in multiple studies has facilitated the evaluation of feeding behavior in individuals with ASD, aiding both researchers and parents in identifying eating difficulties and implementing appropriate interventions [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%